Analysis of Public Figure Prass Teguh Online Identity: Analisis Identitas Daring Tokoh public Prass Teguh - Fani, Mochammad (Universitas Muhammadiyah Sidoarjo, 2025)
Praz Teguh has succeeded in building a strong online persona as an approachable and relevant financial expert. Through a consistent approach and good relationship with the audience, he is able to manage the challenges that arise in his presence in the digital world. However, challenges such as conflicts of interest, weak monitoring of participation, and misinterpretation of messages must be managed carefully so as not to damage the reputation that has been built. This analysis examines how Praz Teguh builds and maintains its online identity, manages interactions with diverse audiences, and faces challenges related to reputation and privacy in the digital world. The results of the analysis show that although Praz Teguh has succeeded in creating a strong online presence, there are opportunities to develop further strategies to protect its reputation and privacy. Highlights: Building a Strong Online Identity – Praz Teguh maintains a consistent and approachable financial expert persona, strengthening audience trust and engagement. Managing Audience Interactions – Effective engagement helps maintain relevance, but challenges like conflicts of interest and message misinterpretation require careful handling. Reputation & Privacy Protection – While his online presence is strong, further strategies are needed to safeguard his reputation and privacy in the digital space. Keywords: Praz Teguh, Online Persona, Finance, Social Media, Community Management, Reputation, Privacy